Crosstalk Between DNA Methylation and Gene Mutations in Colorectal Cancer - Dobre, Maria; Salvi, Alessandro; Pelisenco, Iulia Andreea; Vasilescu, Florina; De Petro, Giuseppina; Herlea, Vlad; Milanesi, Elena (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is often characterized by mutations and aberrant DNA methylation within the promoters of tumor suppressor genes and proto-oncogenes. The most frequent somatic mutations are within KRAS and BRAF genes. Mutations of KRAS gene have been detected in approximately 40% of patients, while BRAF is mutated less frequently at a rate of 10%. In this study the DNA methylation levels of 22 candidate genes have been evaluated in mucosal tumoral tissue from eighteen CRC patients, ten normal adjacent tissue and in a control group of six individuals with a normal colonoscopy. A differential methylation profile of nine genes (RUNX3, SFRP1, WIF1, PCDH10, DKK2, DKK3, TMEFF2, OPCML and SFRP2) presenting high methylation levels in tumoral respect to normal tissues has been identified. KRAS mutations (codons 12 or 13) were detected in eight CRC cases, and BRAF mutations (codon 600) in four cases. One of them presented concomitant mutations in KRAS codon 12 and BRAF, whereas seven patients did not present these mutations (WT). When comparing the methylation profile according to the mutation status, we found that six genes (SFRP2, DKK2, PCDH10, TMEFF2, SFRP1, HS3ST2) showed a methylation level higher in BRAF positive cases than BRAF negative cases. The molecular sub-classification of CRC according to mutations and epigenetic modifications may help to identify epigenetic biomarkers useful to design personalized strategies to improve patients’ outcome.